Contracts, Hold-Up and Labor Markets. - Malcomson, J (School of Social Sciences (University of Southampton), 1997)
The implications for labor markets of contracts to avoid hold-up of investments are assessed. Employment at will protects the returns on a firm's general and specific investments without wages increasing with tenure. With turnover costs, fixed but renegotiable wages can protect general investments by both firm and employee, and generage wage stickiness without adversely affecting employment. Employment contracts that induce efficient specific investments by both firm and employee are problematic so it makes sense, wherever possible, for one side to make all such investments. With private information, fixed wages may induce fewer inefficient separations than employment at will.